2016
DOI: 10.3892/ol.2016.5074
|View full text |Cite
|
Sign up to set email alerts
|

Expression patterns of maspin and mutant p53 are associated with the development of gestational trophoblastic neoplasia

Abstract: Gestational trophoblastic disease (GTD) is a group of conditions that originate from the abnormal proliferation of trophoblastic cells. GTDs encompass hydatidiform moles (HMs) and gestational trophoblastic neoplasia (GTN). GTNs are a group of malignant diseases that require chemotherapy, or more aggressive treatment. There is a requirement for more tumor markers to predict the development of GTN from HMs. The current study evaluated the expression of maspin and tumor protein p53 (p53) in GTD, and their role in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
2
8
0
Order By: Relevance
“…As our data showed, two choriocarcinoma complicated with ETT were negative in the expression of SALL4. Pengming Sun et al [ 20 ] reported that the expression levels of mutant P53 were increased with the development of GTN. The information in our study likewise indicated that patients with P53 positivity had worse outcomes than its negative expression.…”
Section: Resultsmentioning
confidence: 99%
“…As our data showed, two choriocarcinoma complicated with ETT were negative in the expression of SALL4. Pengming Sun et al [ 20 ] reported that the expression levels of mutant P53 were increased with the development of GTN. The information in our study likewise indicated that patients with P53 positivity had worse outcomes than its negative expression.…”
Section: Resultsmentioning
confidence: 99%
“…A genetic role, such as maspin-negative and mutant p53positive expression, is certain in the epidemiology of hydatid form mole, and complete moles appear to have the high risk of subsequent choriocarcinoma and metastasis [11]. In hydatid form mole, serum β-HCG is inversely correlated with maspin expression but is positively correlated with mutant p53 expression [12]. Trophoblast invasion is mediated through the major mediators of implantation, including the matrix metalloproteinase and epidermal growth factor, which transcription is mediated by positive p53 expression [13].…”
Section: Discussionmentioning
confidence: 99%
“…Several attempts have already been developed for early diagnosis and differentiation of GTD different pathologies and the result is promising regarding immunohistochemical methods. According to previous studies, several biomarkers like P53, P57, P63, C-erB-2 (7-10), and maspin (11) have been investigated for such purposes and it has been shown that there was a strong association between P53 and C-erbB-2 expression and tro-phoblastic neoplasia (8). It was also illustrated that these two biomarkers together had high negative predictive values regarding the management of molar pregnancies (8).…”
Section: Introductionmentioning
confidence: 99%